Preparation and characterization of ferrous oxalate cement—A novel acid‐base cement. Issue 2 (21st October 2020) - Luo, Zhongqiu; Ma, Yue; He, Huan; Mu, Weihong; Zhou, Xintao; Liao, Wenyu; Ma, Hongyan
Abstract: Ferrous oxalate cement (FOC), a new type of acid‐base cement, is prepared at room temperature through reactions between iron‐rich copper slag (CS) and oxalic acid (OA). In this work, the influences of precursor proportions, including the copper slag‐to‐oxalic acid mass ratio (CS/OA), borax‐to‐cement mass ratio (B/C), and water‐to‐cement mass ratio (W/C), on the setting behavior and compressive strength of FOC paste are investigated. Furthermore, the evolutions of pH and ions concentrations are traced to understand the reaction mechanism of FOC. The results show that the compressive strength decreases with an increase in W/C; when W/C is fixed, with an increase in CS/OA, the compressive strength first increases and then decreases, giving an optimal value. The compressive strengths of specimens at 3, 7, and 28 days can reach 33, 41, and 55 MPa, respectively, under the optimal conditions (CS/OA = 3.6, B/C = 0.03, and W/C = 0.18). The setting time is also a function of W/C and CS/OA, and can be extended by adding borax. Iron oxalate hydrate (FeC2 O4 ·2H2 O) has been identified as the exclusive hydration product of FOC due to the chemical reaction between Fe2 SiO4 or Fe3 O4 contained in CS and OA solution. At the initial stage of reaction, OA is dissolved to release protons, HC2 O4 − and C2 O4 2−, which facilitate the dissolution of Fe2 SiO4 and Fe3 O4 and the release of Fe 2+ in the aqueous phase. Then the Fe 2+ ions combine with HC2 O4 − and C2 O4 2− to precipitate FeC2 O4 ·2H2 O, acting as the cementitious phase to bond the unreacted CS particles.